Miocene stratigraphy : an integrated approach - Montanari, Alessandro; Odin, Gilles S.; Coccioni, R. (Developments in palaeontology and stratigraphy ;, 1997)
This book constitutes an excellent and probably unique example of how interdisciplinary stratigraphic and geochronologic studies are approached with modern methodologies and techniques. It contains numerous unpublished, accurate radioisotopic dates of volcano-sedimentary layers interbedded in fossiliferous marine and continental Miocene sequences representing Mediterranean and Pacific environments. New, extremely detailed paleontologic data which constitute the basis for an accurate definition of the Miocene biostratigraphy, and the study of the ecologic evolution of Miocene marine environments are also included. The chapters are complimented by black-and-white photographs, graphic figures, and tables. Stratigraphers, paleontologists and sedimentologists plus geologists working in oil companies will certainly find this work of interest.